Alih Kode dan Campur Kode pada Tindak Tutur Guru-Guru di SMAN 1 Panti Pasaman Perspektif Sosiolinguistik - Gustiana; Syofiani Syofiani; Yetty Morelent (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to examine: (1). What are the forms of code switching and code mixing in the speech acts of teachers at SMAN 1 Panti Pasaman, (2). What are the types of code switching and code mixing in the speech acts of teachers at SMAN 1 Panti Pasaman, (3). What are the functions of code switching and code mixing carried out by speakers in the speech acts of teachers at SMAN 1 Panti Pasaman, and (4). What are the factors that cause the occurrence of code switching and code mixing in the speech acts of teachers at SMAN 1 Panti Pasaman. In this case, the author uses a qualitative research method, while the method used is a descriptive method, namely a method that describes the things to be studied in the form of words. This study is very suitable for describing and processing data in research so that it can become an interesting descriptive description. Several reasons are used for a qualitative approach in this study. This study will be directed at Code Switching and Code Mixing in the Speech Acts of Teachers at SMAN 1 Panti Pasaman from a Sociolinguistic Perspective. Want to ensure the accuracy of the data. Because social data is difficult to verify without knowing what it means.